Machine learning modeling of cancer treatment-related cardiac events in breast cancer: utilizing dosiomics and radiomics - Dincer, Sefika; Akmansu, Muge; Akyol, Oya (Frontiers in Oncology, 2025)
BackgroundPersonalized medicine has transformed disease management by focusing on individual characteristics, driven by advancements in genome mapping and biomarker discoveries.Objectives:This study aims to develop a predictive model for the early detection of treatment-related cardiac side effects in breast cancer patients by integrating clinical data, high-sensitivity Troponin-T (hs-TropT), radiomics, and dosiomics. The ultimate goal is to identify subclinical cardiotoxicity before clinical symptoms manifest, enabling personalized surveillance strategies. It is the first study to utilize heart-segmented dosiomics in breast cancer patients.Methods and MaterialsThis retrospective study included clinical, dosimetric, radiomic, and dosiomic data from 42 women with localized breast cancer. Heart-specific Troponin T levels were measured 2–3 weeks post-radiotherapy, with 14 ng/L as the cutoff. Patients were grouped on this threshold to identify potential treatment-related cardiac events. Radiomics and dosiomics were extracted using PyRadiomics. Machine learning models were optimized using the Tree-based Pipeline Optimization Tool (TPOT), identifying the gradient-boosted classification as the best-performing algorithm. Feature selection was conducted using gradient-boosted recursive feature elimination. Model performance is assessed by the area under the curve (AUC).ResultsA total of 111 dosiomic and 119 radiomic features were extracted per patient. The highest predictive accuracy was achieved using clinical, dosiomic, and radiomic parameters (validation cohort-AUC = 0.96), outperforming the clinical + dosimetric model (validation cohort-AUC = 0.67). Permutation tests confirmed the non-randomness of these two models results (p <0.05). Cross-validation indicated that the clinical + dosiomic + radiomic model had a fair-to-good generalizable performance (mean AUC = 80.33 ± 21%).DiscussionThis study may demonstrate that radiomics and dosiomics provide superior predictive capabilities for cardiac events in breast cancer patients compared to traditional parameters.